Gender, socioeconomics status and maturation differences in pubertal children’s physical activity - Barbosa, Tiago M. (1999)
The purpose of this study was to identify differences in the physical activity of pubertal children according to their gender, their socioeconomics status (SES) and their stage of maturation (SM).